DEVELOPMENT OF AR-COMIC DIGITAL BOOK BASED ON PANCASILA STUDENT PROFILE TO ENHANCE LEARNING INDEPENDENCE - Tria Aditia Nugraha; Zakiyah Ismuwardani; Mochamad Guntur; Hilda Safitri; Amanda Maharani (Program Studi PGSD Universitas Flores, 2026)
This study aims to develop an Augmented Reality-Comic Digital Book based on the Pancasila Student Profile to enhance learning independence. The research employs the Research and Development (R&D) methodology, utilizing the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The R&D process involves expert validation and effectiveness testing, using questionnaires and an independent sample t-test with 51 fifth-grade students. The findings indicate that the media is classified within the